PENGARUH PARTISIPASI ANGGARAN TERHADAP PENINGKATAN KINERJA MANAJERIAL DENGAN PSYCHOLOGICAL CAPITAL DAN BUDAYA ORGANISASI SEBAGAI VARIABEL INTERVENING - Iroh Rahmawati (Progress: Jurnal Pendidikan, Akuntansi dan Keuangan, 2019)
This study was conducted to determine the effect of budget participation on managerial performance with psychological capital and organizational culture as an intervening variable. The data to be used in this study are primary data obtained through questionnaires.. Respondents were selected by random sampling method with the following criteria: have a minimum education S1, has experience in the field of budget for at least one year actively involved in the budgeting process, large-scale manufacturing company with employees more than 300 people, and the total assets owned by the company over one hundred billion. The sample used in this study were 115 respondents manager of a manufacturing company in the Province of Banten. Data analysis was performed using Partial Least Square (PLS). The study provides empirical evidence that there is a positive effect of budget participation at psychological capital, the positive influence of budget participation on culture organization, the positive influence of budget participation on managerial performance, the positive influence of psychological capital on managerial performance, and the positive influence of organizational culture on managerial performance. Result This study also shows the role of psychological and cultural capital No organization as variables mediating the effect of budget participation on managerial performance.